KETERASINGAN ORANG TURKI DI JERMAN DALAM ROMAN REMAJA BERBAHASA JERMAN YILDIZ HEIβT STERN KARYA ISOLDE HEYNE - Okky Dwi Hapitta (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2019)
The increasing number of Turks who came to Germany led to the formation of new social groups in Germany. The presence of Turkish people and social groups, adds a distinctive impact to the social life of Germans. One of the resistance movements of certain groups who did not like the presence of Turks in Germany was carried out by Skinheads who were subcultures of Neo-Nazi. The Skinhead group's rejection of the Turks made foreigners feel alienated in Germany. The alienation felt by Turks is the background of Isolde Heyne in writing this teenage novel entitled Yildiz Heiβt Stern (1994).The forms of alienation in the novel narrative are a form of racism. The Turks also experience alienated and strange feelings in Germany. In this study, I used the concept of othering as stated by Gayatri Spivak (2008).